ANALISIS COURSE STABILITY INDEX PADA KAPAL DI PERAIRAN DANGKAL - Axela Putri Chumaira, (2023)
The calculation of the Course Stability Index (CSI) is one of the important parameter for evaluating a ship's maneuvering capability while sailing and avoiding disturbances at sea, thereby enhancing its safety. CSI is influenced by several factors, including: ship draft, water depth, loading condition, hull shape, speed, and trim/sink conditions. The differences in loading condition (full load, half load, ballast) are considered to assess the ship's maneuvering capability under various conditions, as ships do not always operate at full load capacity. This research used an LCT (Landing Craft Tank) Ship with principal dimensions: LPP 53 m, B 13.50 m, d 2.90 m, and Cb 0.802 which were calculated in deep waters and shallow waters. This research used numerical simulation of mathematical models as its method. CSI is considered stable if the calculation results are negative (-), otherwise if the results are positive (+), then CSI is considered unstable. The calculation results show that ship's maneuverability in deep waters under conditions of full load 0.011958, half load 0.010709, and ballast 0.009389. As for the ship's maneuverability in shallow waters, the results obtained at full load -0.019056, half load 0.009990, and ballast 0.019647. Based on the results, the maneuverability of the LCT Ship is only stable under full load conditions in shallow waters, which is -0.019056, while for other two conditions in deep waters and shallow waters, results showed that the ship is less stable.